Administrative policy of the Interior Ministers of the Republic of Poland in the field of provisioning and its impact on the provisioning of the Polish army in 1918–1939 - Kozyra, Waldemar (Armia kontra natura, 2020)
It should be noted that in the Republic of Poland in the years 1918–1939 the main state institutions in the field of provisioning were: in the period of 1918–1921 the Ministry of Provisioning, in the years 1921–1938 the Ministry of the Interior, and in the years 1938–1939 the Ministry of Agriculture and Agricultural Reforms. Of course, in the entire interwar period for the provision of state supplies, and especially its main supply subsystems, such as urban population (various categories of cities and settlements), rural population (individual regions of the country), Polish army, public administration, state enterprises, industrial plants, etc. many specialized state (administrative) institutions, self-government structures, business entities and social organizations worked. However, it should be emphasized with all force that the concepts of the provisioning policy, and then the forms and methods of its implementation arose in the central and supreme institutions of the state, which, by virtue of government laws and ordinances, received competences in this respect. It should be recalled that for a great part of the interwar period the supreme state institution in the field of food supply policy was the Ministry of the Interior. Therefore, without knowing the twists and turns of the administrative policy of the Interior Ministers in the field of food supply, it is impossible to understand the ways of provisioning the society during the Second Polish Republic, and especially the forms, methods and problems related to the provisioning of the Polish Army. Finally, it should be noted that the provisioning system of the Polish State – starting from its very beginning – has although sometimes with difficulty, coped with not only the burden of provisioning the Polish society with food and necessities, but also the provisioning of the Polish army during the wars (1918–1921), during peace (1921–1939) as well as during the German-Polish war of 1939.